Manuals on Macroeconomic Statistics : A Stocktaking to Guide Future Work - Carson, Carol (IMF Working Papers; Working Paper, 2001)
Over the last decade, a number of methodological manuals on macroeconomic datasets were produced by the international community. For a number of reasons, these manuals could be viewed as fragmented, disconnected, and branching in various directions. This paper groups by topics and broad classifications a critical mass (some 40) of manuals that have been published since 1993 or that are nearing completion. Viewing the manuals in an integrated framework prompts a reflection with four broad types of issues to be addressed for future work: awareness and accessibility of the manuals; their relevance; the need for further harmonization, and the need for updating procedures.